High-power lithium ion batteries based on flexible and light-weight cathode of LiNi0.5Mn1.5O4/carbon nanotube film. (March 2015) - Fang, Xin; Shen, Chenfei; Ge, Mingyuan; Rong, Jiepeng; Liu, Yihang; Zhang, Anyi; Wei, Fei; Zhou, Chongwu
Abstract: We report the integration of high voltage cathode material LiNi0.5 Mn1.5 O4 and multiwall carbon nanotube network for the first time, which has led to charge/discharge rate as high as 20C and has also been demonstrated to work as cathode for flexible batteries. The LiNi0.5 Mn1.5 O4 / multiwall carbon nanotube network is flexible and light-weight since the use of binder, conductive additive and metal current collector is eliminated. Due to the high voltage provided by LiNi0.5 Mn1.5 O4 particles, the total energy of the battery is significantly enhanced. In addition, with the high conductivity from multiwall carbon nanotube network, the LiNi0.5 Mn1.5 O4 /multiwall carbon nanotube network electrodes can deliver 80% of the 1C capacity even when the charge/discharge current density increased to 20C (1C=140 mA/g). During the high current rate cycling test, no obvious capacity decay is observed after 100 cycles at 10C. Calculation of the polarization resistance R p reveals that the R p of the LiNi0.5 Mn1.5 O4 /multiwall carbon nanotube electrodes is less than 25% of that of the conventional electrodes fabricated through slurry-casting on metal current collector. In addition, the power density calculated from LiNi0.5 Mn1.5 O4 /multiwall carbon nanotube electrodes is over two times larger than that provided by the conventional electrodes. The combined effect from high voltage, high current rate performance and reduced weight has led our LiNi0.5 Mn1.5 O4 /multiwall carbon nanotube electrodes to be a promising candidate for high-power lithium ion batteries. Moreover, the features of flexibility and light-weight also demonstrate the potential of applying the LiNi0.5 Mn1.5 O4 / multiwall carbon nanotube electrodes in new-generation flexible or ultrathin/ultralight electronic devices in the future. Graphical abstract: Highlights: High power Li-ion battery is achieved using LiNi0.5 Mn1.5 O4 / MWCNT cathode Power density is two times enhanced by LiNi0.5 Mn1.5 O4 / MWCNT cathode LiNi0.5 Mn1.5 O4 / MWCNT cathode can deliver 80% of 1C capacity at 20C charge/discharge No obvious capacity degradation is observed after 100 cycles charge/discharge at 10C LiNi0.5 Mn1.5 O4 / MWCNT cathode is good for flexible and light-weight batteries